Oxygen isotopes in subducted oceanic crust: A new perspective from Siberian diamondiferous eclogites. (3rd September 2013) - Carmody, Laura; Barry, Peter H.; Shervais, John W.; Kluesner, Jared W.; Taylor, Lawrence A.
<x xml:space="preserve">Abstract</x> [1] There are three methods of investigating the oxygen‐isotope composition of oceanic crust: (1) data from drilling‐obtained samples; (2) study of obducted ophiolites; and (3) from crustal‐derived xenoliths; however, each approach has limitations. Drilling capabilities are limited to the upper 1–3 km of the oceanic crust. Ophiolites are segments of oceanic crust and underlying mantle exposed at the Earth's surface, but their origin and emplacement are still debated. Nonetheless, the study of ophiolite sequences has enabled many of the fundamental observations regarding ancient‐oceanic crust and the oxygen‐isotope signature of the upper mantle. Analyses of ophiolite sequences (e.g., Samail) reveal δ18O variations ranging from isotopically enriched in relation to MORB (δ18O > MORB) to isotopically depleted (low δ18O ≤ MORB), interpreted to show the effects of seawater interaction at different temperatures. Mantle‐derived xenoliths also display compelling geochemical evidence suggesting they are remnants of subducted ocean crust, and may in fact, be more representative samples. Some kimberlite‐hosted diamondiferous eclogite xenoliths, with crustal protoliths, reveal a marked oxygen‐isotope disparity between oceanic crust and the upper mantle; i.e., a bimodal distribution of both mantle‐like (δ18O ≈ 5.6‰) and isotopically enriched oxygen (δ18O ≈ 6.8‰). The isotopically high δ18O values are often observed in eclogite xenoliths with ultramafic protoliths, which form beyond the low‐temperature alteration zone. This finding is in contrast to traditional oxygen‐isotope versus depth‐curves of ophiolite sequences. Here, we present a compiled data set from Siberian eclogites and pyroxenites that illustrates this bimodality, using magnesium number (Mg#) as a depth proxy, and investigate the conditions that could potentially result in the observed "abnormal" oxygen‐isotope variations.